The bottom-up information transfer process and top-down attention control underlying tonal working memory - Li, Qiang; Gong, Dinghong; Zhang, Yuan; Zhang, Hongyi; Liu, Guangyuan (Frontiers in Neuroscience, 2022)
We analyzed the dynamic cortical processing process of tonal working memory with an original surface-space-based multivariate pattern analysis (sf-MVPA) method and found that this process constituted a bottom-up information transfer process. Then, the local cortical activity pattern, local cortical response strength, and cortical functional connectivity under different tonal working memory loads were investigated. No brain area’s local activity pattern or response strength was significantly different under different memory loads. Meanwhile, interactions between the auditory cortex (AC) and an attention control network were linearly correlated with the memory load. This showed that the neural mechanism underlying tonal working memory load does not arise from changes in local activity patterns or changes in local response strength, but from top-down attention control. Our results indicate that the implementation of tonal working memory is based on the cooperation of the bottom-up information transfer process and top-down attention control.